Multiple scattering dynamics of fermions at an isolated p-wave resonance - R. Thomas (Nature Portfolio, 2016)
Multiple scattering with wave-like atoms is known to produce non-trivial many-body effects. Here, the authors investigate multiple scattering in the semi-classical limit using deviations in the scattering halos produced by the collision of indistinguishable ultracold fermions.